Supramolecular elastomers. Particulate β-sheet nanocrystal-reinforced synthetic elastic networks. (14th July 2017) - Yan, Xuesong; Jin, Hailiang; Fahs, Gregory B.; Chuang, Steven; Moore, Robert B.; Jia, Li
Abstract: Tris- and tetra-(β-alanine)-grafted polyisobutylenes (A3 andA4 ) with the same grafting density have been synthesized and studied. IR, DSC, SAXS, and WAXD show that the β-alanine tetramer segments inA4 form β-sheet crystals similar to those inA3 .A3 andA4 are melt-processable TPEs. The less than 5% by volume of β-sheet crystals inA3 andA4 bring about mechanical properties significantly better that those of a vulcanized butyl rubber composite optimally reinforced with carbon black (CBV ).A4 is somewhat stiffer and less extensible thanA3 . Overall, only a small gain in toughness is achieved forA4 overA3 . Importantly, A3 andA4 also show hysteretic properties and dynamic mechanical properties superior toCBV . BothA3 andA4 are less hysteretic thanCBV at low strains and more hysteretic at high strains. Their loss factors are substantially lower than that ofCBV in the temperature range of 60–100 °C, and their modulus dependence on strain amplitude at very low strains (Payne effect) are significantly subdued in comparison toCBV . In fact, A3 is slightly better thanA4 in all respects from the view point of hysteresis and dynamic mechanical properties. Dichroic IR study indicates that the oligo(β-alanine) segments inA3 andA4 statistically prefer to orient perpendicular to the extension axis due to shear stress exerted on the elongated β-sheet crystals at <250% strain. At higher strains, the grafting molecular architecture and the random location of the load-bearing chain on the surface of the β-sheet crystals dictate the orientation of the β-sheet crystals to be random. No fragmentation of the β-sheet crystals in the hydrogen-bonding direction is detectable during the entire process of extension until break. The residual preference of the oligo(β-alanine) segments for the orientation perpendicular to the extension axis is attributed to the elongated β-sheet crystal morphology, which prevent the crystals from fully comply to the load-bearing chains. Graphical abstract: Highlights: Thermoplastic elastomers physically crosslinked and reinforced by particulate β-sheet nanocrystals are highly extensible and highly stiff at the same time. Dynamic mechanical properties of such thermoplastic elastomers are superior to those of its vulcanized analog reinforced by carbon black. The particulate β-sheet nanocrystals undergo first orientation by shear and then disorientation by load-bearing strands during extension. Fragmentation of the β-sheet crystals is not detectable in the hydrogen-bonding direction and hence, by inference, must be in the sheet-stacking direction during extension.